2015
DOI: 10.1016/j.joca.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Soluble factors from the notochordal-rich intervertebral disc inhibit endothelial cell invasion and vessel formation in the presence and absence of pro-inflammatory cytokines

Abstract: Background Chronic low back pain can be associated with the pathological ingrowth of blood vessels and nerves into intervertebral discs (IVDs). The notochord patterns the IVD during development and is a source of anti-angiogenic soluble factors such as Noggin and Chondroitin sulfate (CS). These factors may form the basis for a new minimally invasive strategy to target angiogenesis in the IVD. Objective To examine the anti-angiogenic potential of soluble factors from notochordal cells (NCs) and candidates Nog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
2
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 53 publications
0
74
2
2
Order By: Relevance
“…In this study, VEGF and Ang‐1 was up‐regulated in perforated disk cells like other cartilage angiogenesis, including intervertebral disk and TMJ cartilage . In TMJ disk, the invaded vessels are formed from pre‐existing ones which are mainly at disk periphery, such as retrodiscal tissues.…”
Section: Discussionmentioning
confidence: 67%
“…In this study, VEGF and Ang‐1 was up‐regulated in perforated disk cells like other cartilage angiogenesis, including intervertebral disk and TMJ cartilage . In TMJ disk, the invaded vessels are formed from pre‐existing ones which are mainly at disk periphery, such as retrodiscal tissues.…”
Section: Discussionmentioning
confidence: 67%
“…Similarly, other studies have demonstrated increased proteoglycan synthesis in NP cells treated with notochordal cell derived conditioned medium (NCCM) in vitro 22. A recent study also demonstrated the anti-angiogeneic effects of NCCM in vitro 23. These studies provide compelling evidence that NCs secrete proteins, which may confer anabolic characteristics, maintain a homeostatic microenvironment in NP and resists DDD.…”
mentioning
confidence: 64%
“…Fas ligand, a type II transmembrane protein of the tumor necrosis factor family, expressed by normal NP cells, could cause apoptosis in vascular endothelial cells and subsequently inhibit blood vessel infiltration (Sun et al ., 2013). Additionally, Nog and chondroitin sulfate released from notochordal cells inhibited angiogenesis by suppressing vascular endothelial growth factor signaling (Cornejo et al ., 2015). Nerves in the discs, either accompanying the vessels or occurring independently, are branches of the sinuvertebral nerve or the gray rami communicantes (Johnson et al , 2001; Raj, 2008).…”
Section: Vascular Neural and Basic Anatomymentioning
confidence: 99%